Thermal equilibrium and prehydration processes of electrons injected into liquid water calculated by dynamic Monte Carlo method. (October 2015) - Kai, Takeshi; Yokoya, Akinari; Ukai, Masatoshi; Fujii, Kentaro; Watanabe, Ritsuko
Abstract: The thermalization length and spatial distribution of electrons in liquid water were simulated for initial electron energies ranging from 0.1 eV to 100 keV using a dynamic Monte Carlo code. The results showed that electrons were decelerated for thermalization over a longer time period than was previously predicted. This long thermalization time significantly contributed to the series of processes from initial ionization to hydration. We further studied the particular deceleration process of electrons at an incident energy of 1 eV, focusing on the temporal evolution of total track length, mean traveling distance, and energy distributions of decelerating electrons. The initial prehydration time and thermalization periods were estimated to be approximately 50 and 220 fs, respectively, indicating that the initial prehydration began before or contemporaneously with the thermal equilibrium. Based on these results, the prehydrated electrons were suggested to play an important role during multiple DNA damage induction. Highlights: Electron deceleration process in liquid water was calculated. Thermalization lengths calculated is consistent with previously experimental ones. Initial prehydration may begin contemporaneously with the thermal equilibrium.